Historic data analysis reveals ambient temperature as a source of phenotypic variation in populations of the land snail Theba pisana. (15th March 2013) - Köhler, Heinz‐R.; Schultz, Carolin; Scheil, Alexandra E.; Triebskorn, Rita; Seifan, Merav; Di Lellis, Maddalena A.
<x xml:space="preserve">Abstract</x> Pulmonate land snails are often polymorphic in their shell coloration pattern. To quantify the contribution of environmental parameters to the nondirectional change in phenotypic variation, we used a historic dataset on Theba pisana morph frequencies and climate data for statistical modelling. We found significant correlations of the degree of phenotypic diversity between juveniles and corresponding adult individuals within the same and the subsequent generation. Among climate parameters, the phenotypic diversity of adults correlated significantly and positively with the mean and maximum ambient temperatures in the winter and spring only. There was no correlation between high or low temperatures and the frequency of distinct morphs. Akaike's information criterion‐based model selection revealed the particular importance of only parental phenotypic diversity for next generation juvenile phenotypic diversity. By contrast, phenotypic diversity of the juveniles of the preceding year and the mean temperatures in winter and spring were important for the phenotypic diversity of adult snails. Approximately two‐thirds of the explicable variation in phenotypic diversity of adults was explained by inheritance and approximately one‐third was expained by ambient temperature. The present study shows that genetics and temperature interact to generate nondirectional changes in phenotypic variation within populations, which also can be reflected by changes in the phenotype of individuals. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 109, 241–256.